Powder basalt, development and nutrition of common bean (Phaseolus vulgaris) and chemical properties of a sandy loam Humic Cambisol (Revista de Ciências Agroveterinárias, 2009)
The objective of this work was to study the potential use of basalt powder rock as a source of nutrients for common bean, associated or not to bovine farmyard, and their effect on soil chemical properties, plant nutrition and the crop productivity. The experiment was set in Lages, SC, in a sandy loam Humic Cambisol, using a completely randomized design. Two kinds of basalt, from Ponte Alta and São José do Cerrito, SC, Brazil, were evaluated. The pH of the area was corrected with lime for 5.2. P and K were supplied by the addition of natural sources (granite - K; apatite - P), except in the treatment with NPK. The treatments were: liming of pH 5.2, NPK, bovine farmyard 3 Mg ha-1, Basalt Batalhão (BBT) and Ponte Alta (BPA) in the rates to 2.5, 5 and 10 Mg ha-1 and the same rates associated to the addition of bovine farmyard (3 Mg ha-1, dry weight basis). Treatments were applied over the plots and incorporated with rotatory hoe. The black bean cultivar Uirapuru was used as a test crop. Grain yield and leaf analysis of macro and micronutrients of common bean were determined. The values of P, K, Ca, Mg, pH, H + Al and soil organic matter were also assessed. The treatment that promoted the highest grain yield was BPA in the level of 10 Mg ha-1 + farmyard. The pH increased from 4.7 to values that ranged between 5.1 to 5.6, without showing differences among treatments, evidencing only the effect of lime on the partial correction of acidity. The values of Ca and Mg increased in the soil. The P presented high values, however its behavior should to be interpreted with care, because natural phosphate was applied and the acid extractor utilized (Mehlich 1) tends to overestimate the content of soluble P. Macro and micronutrients in the leaf were in the sufficiency zone for common bean. Ca, Mg and Zn didn't present statistics differences among treatments in the soil or inside the plant. The lack of positive effect of powdered basalt application on common bean grain yield was possibly due the weather dry conditions and the short period for liberation of nutrients, because powder rocks present slow mineral dissolution.
Keywords: powder rock; natural manuring; bovine farmyard; nutrition of bean.